Negative electrode, method for manufacturing same, non-aqueous electrolyte secondary battery comprising

CN119581484APending Publication Date: 2025-03-07PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411198945.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-07
Filing Date
2024-08-29
Publication Date
2025-03-07

Smart Images

  • Figure CN119581484A_ABST
    Figure CN119581484A_ABST
Patent Text Reader

Abstract

A negative electrode for a non-aqueous electrolyte secondary battery has an active material layer containing active material particles. The active material particles include carbon-based active material particles and metal-based active material particles. The active material layer has a connecting part that connects two of the active material particles. The connecting part has a first layer containing polyacrylic acid and / or a salt thereof, and a second layer formed on the surface of the first layer and containing styrene-butadiene rubber. Both the first layer and the second layer are in contact with the surfaces of the two active material particles connected by the connection portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode and a method for producing the same, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for producing the same. Background Art

[0002] In order to increase the capacity of the negative electrode of a non-aqueous electrolyte secondary battery, it is known that graphite and SiO2 can achieve a higher capacity than graphite. x Si-based active materials are used together (Japanese Patent Publication No. 2015-53152 and International Publication No. 2017 / 026268, etc.). Compared with graphite, Si-based active materials expand and shrink greatly with the charge and discharge of secondary batteries, so it is easy to cause a decrease in the electronic conductivity in the active material layer, and the capacity retention rate after the charge and discharge cycle is easy to decrease.

[0003] Japanese Patent Publication No. 2015-53152 discloses that polyacrylic acid is used to suppress the expansion and contraction accompanying the charge and discharge of a secondary battery. International Publication No. 2017 / 026268 discloses that a coating layer of polyacrylic acid is formed in a carbon-based active material and a Si-based active material, and the content ratio of polyacrylic acid is optimized to suppress the expansion of the secondary battery and suppress the decrease in discharge capacity. Summary of the invention

[0004] Secondary batteries are required to have further improved cycle characteristics. The present disclosure aims to provide a negative electrode capable of obtaining a secondary battery having excellent cycle characteristics, a method for producing the negative electrode, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for producing the same.

[0005] [1] A negative electrode for a non-aqueous electrolyte secondary battery, comprising an active material layer containing active material particles.

[0006] The active material particles include carbon-based active material particles and metal-based active material particles.

[0007] The active material layer has a connecting portion connecting two of the active material particles.

[0008] The connecting portion comprises a first layer and a second layer, the first layer comprises at least one of polyacrylic acid and a salt thereof, and the second layer is formed on a surface of the first layer and comprises styrene-butadiene rubber.

[0009] The first layer and the second layer are both in contact with the surfaces of the two active material particles connected by the connecting portion.

[0010] [2] The negative electrode according to [1], wherein the carbon-based active material particles include graphite particles.

[0011] [3] The negative electrode according to [1] or [2], wherein the metal-based active material particles include a metal selected from Si, SiO x and one or more particles of a complex of Si and C.

[0012] [4] The negative electrode according to any one of [1] to [3], wherein the connecting portion connects at least the carbon-based active material particles and the metal-based active material particles.

[0013] [5] The negative electrode according to any one of [1] to [4], wherein the active material layer further contains a conductive auxiliary agent.

[0014] [6] The negative electrode according to any one of [1] to [5], wherein the active material layer further contains carboxymethyl cellulose.

[0015] [7] A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of [1] to [6].

[0016] [8] A method for producing a negative electrode, which is a method for producing a negative electrode for a non-aqueous electrolyte secondary battery, wherein the negative electrode has an active material layer containing active material particles.

[0017] The negative electrode manufacturing method comprises: a first step of obtaining a kneaded body, a second step of obtaining a slurry using the kneaded body, and a third step of forming the active material layer using the slurry.

[0018] The first step includes kneading the active material particles, polyacrylic acid hydrate and water, wherein the polyacrylic acid hydrate is obtained by hydrating at least one of polyacrylic acid and a salt thereof.

[0019] The active material particles include carbon-based active material particles and metal-based active material particles.

[0020] The second step includes adding styrene-butadiene rubber and water to the kneaded mass and kneading the mixture.

[0021] When water is added to a mixture obtained by mixing at least one of the polyacrylic acid and its salt and the active material particles at a ratio contained in the kneaded body and kneading, the solid content ratio at which the torque reaches a maximum is defined as an ideal solid content ratio B0 [wt %],

[0022] The solid content ratio of the kneaded body is (B0-5) to B0 [weight %],

[0023] The solid content ratio of the above slurry is (B0-25) to (B0-10) [wt %].

[0024] [9] The method for producing a negative electrode according to [8], wherein the kneading step in the first step is performed by further adding carboxymethyl cellulose.

[0025]

[10] The method for producing a negative electrode according to [8] or [9], wherein the kneading step in the first step is performed by further adding a conductive auxiliary agent.

[0026]

[11] The method for producing a negative electrode according to any one of [8] to

[10] , wherein the carbon-based active material particles include graphite particles.

[0027]

[12] The method for producing a negative electrode according to any one of [8] to

[11] , wherein the metal-based active material particles contain a metal selected from Si, SiO x and one or more particles of a complex of Si and C.

[0028]

[13] A method for producing a non-aqueous electrolyte secondary battery, comprising the step of producing a negative electrode using the method for producing a negative electrode described in any one of [8] to

[12] .

[0029] The above and other objects, features, aspects and advantages of the present invention will become more apparent from the following detailed description of the present invention when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 1 is a flowchart showing a method for producing a negative electrode according to an embodiment.

[0031] Figure 2 This is a scanning transmission electron microscope image of the active material layer obtained in Example 1.

[0032] Figure 3 This is a scanning transmission electron microscope image of the active material layer obtained in Example 2.

[0033] Figure 4 This is a scanning transmission electron microscope image of the active material layer obtained in Comparative Example 1.

[0034] Figure 5 This is a scanning transmission electron microscope image of the active material layer obtained in Comparative Example 2. DETAILED DESCRIPTION

[0035] In this specification, unless otherwise specified, the numerical range of "x to y" includes the upper limit and the lower limit. That is, "x to y" means a numerical range of "above x and below y". A numerical value arbitrarily selected from the numerical range can be used as a new upper limit or lower limit. For example, a new numerical range can be set by arbitrarily combining the numerical values ​​in the numerical range with the numerical values ​​recorded in other parts, tables, or figures in this specification.

[0036] (negative electrode)

[0037] The negative electrode of the present embodiment (hereinafter also referred to as "the present negative electrode") is a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery"), and has an active material layer containing active material particles. The active material particles include carbon-based active material particles (hereinafter also referred to as "carbon-based particles") and metal-based active material particles (hereinafter also referred to as "metal-based particles"). The active material layer has a connecting portion connecting two active material particles. The connecting portion has a first layer and a second layer, the first layer containing at least one of polyacrylic acid and its salt (hereinafter also referred to as "PAA"), and the second layer is formed on the surface of the first layer and contains styrene-butadiene rubber (hereinafter also referred to as "SBR"). The first layer and the second layer both contact the surfaces of the two active material particles connected by the connecting portion.

[0038] The carbonaceous particles as active material particles preferably contain particles of one or more selected from carbon materials such as graphite, hard carbon, soft carbon and amorphous coated graphite, or are particles of one or more selected therefrom, and preferably contain graphite particles or are graphite particles.

[0039] The metal particles as active material particles include particles of metal elements such as metal monomers or metal oxides, and the metal monomers include an element selected from silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). The metal particles preferably include an element selected from Si, SiO x (x=0.5 to 1.5), a composite of Si and C (hereinafter also referred to as "SiC composite"), and Sn, or one or more particles selected therefrom, more preferably particles selected from Si, SiO x , and SiC composite particles, or one or more particles selected therefrom. The metal-based particles are more preferably SiC composite particles. The SiC composite is, for example, a composite in which Si is dispersed in a carbon matrix.

[0040] The average particle size D50 of the metal particles is, for example, 3 to 15 μm, preferably 5 to 10 μm. The average particle size D50 in this specification refers to the particle size at which the frequency of the particle with the smallest particle size in the volume-based particle size distribution reaches 50%. The volume-based particle size distribution can be measured using a laser diffraction particle size distribution measuring device.

[0041] The total content of carbon-based particles and metal-based particles contained in the active material particles may be 90 to 100 weight percent, 90 to 99 weight percent, or 92 to 95 weight percent relative to the total amount of active material particles. The ratio of carbon-based particles to metal-based particles in the active material particles may be 70:30 to 95:5, 80:20 to 92:8, or 85:15 to 95:5 (weight ratio).

[0042] The present negative electrode may have an active material layer on a negative electrode current collector. The active material layer may be formed on only one side of the negative electrode current collector or may be formed on both sides. The negative electrode current collector is, for example, a metal foil made of a copper material such as copper or a copper alloy.

[0043] When the active material layer is formed on both sides of the negative electrode current collector, the weight per unit area of ​​the active material layer on both sides (total of both sides) can be, for example, 150 to 250 g / m 2 , can be 170~230g / m 2 , can also be 180~220g / m 2 . The weight per unit area of ​​each single side of the negative electrode collector may be, for example, half of the weight per unit area of ​​each of the two sides mentioned above. The thickness per single side of the active material layer may be, for example, 90 to 200 μm, 100 to 180 μm, or 110 to 150 μm. The packing density of the active material layer may be calculated by the following formula, and may be, for example, 1.3 to 1.9 g / cc, 1.4 to 1.8 g / cc, or 1.5 to 1.7 g / cc.

[0044] Packing density [g / cc] = weight per unit area of ​​active material layer [g / m 2 ] / Thickness of active material layer [μm]

[0045] The active material layer has a connecting portion, and the connecting portion connects two active material particles in the active material layer. By having a connecting portion, the active material layer can be in a state where a conductive path is easily formed between the active material particles with the help of a conductive auxiliary agent or the like. The connecting portion of the present negative electrode has a first layer and a second layer formed on the surface of the first layer. In the present negative electrode, both the first layer and the second layer contact the surface of the active material particles, so the connecting portion can connect the active material particles using both the first layer and the second layer. That the connecting portion has the first layer and the second layer can be confirmed, for example, by a scanning transmission electron microscope image (hereinafter also referred to as a "SEM image") or observation of the spectral distribution based on SEM-EDX (energy dispersive X-ray spectroscopy).

[0046] The length of the connecting portion (the distance in the direction connecting two active material particles) can be 0.1 to 5 μm, 0.5 to 4 μm, or 1 to 3 μm. The diameter of the connecting portion can be 0.1 to 1 μm, 0.2 to 0.9 μm, or 0.3 to 0.8 μm. The length and diameter of the connecting portion can be determined by analyzing the SEM image.

[0047] The first layer includes PAA. PAA can be in the form of an acid (polyacrylic acid), can be in the form of a salt (polyacrylate), or can include both, but preferably includes the form of a salt. PAA is preferably in the form of a salt. As the salt, alkali metal salts such as potassium and sodium can be cited. PAA has excellent adhesion and is easy to impart mechanical strength (hardness) to the connecting portion while maintaining the distance between the two active material particles. Thus, even if the active material particles expand and shrink with the charge and discharge of the secondary battery, it is possible to ensure that the distance between the two active material particles is small, so it is easy to ensure the conductivity of the active material layer.

[0048] The second layer can be formed on the surface of the first layer, preferably in a manner that covers the entire surface of the first layer, and can cover the first layer in a manner that the surface of the first layer is not exposed. The second layer contains SBR. Since SBR has excellent flexibility, it can form a connection portion that follows the expansion and contraction of the active material particles accompanying the charge and discharge of the secondary battery.

[0049] As described above, the connecting portion has the first layer and the second layer, and compared with the connecting portion formed in a state where PAA and SBR are mixed, even if the active material particles expand and shrink with the charge and discharge of the secondary battery, it is possible to ensure that the distance between the active material particles is small, and a connecting portion that is not easy to disconnect can be formed. In addition, the connecting portion can also connect two active material particles arranged at a distant position in the active material layer. Thus, a conductive path is easily formed in the active material layer with the aid of a conductive auxiliary agent, so that a secondary battery with excellent cycle characteristics is easily obtained. The connecting portion having the first layer and the second layer is obtained, for example, by a method for manufacturing a negative electrode described later.

[0050] The two active material particles connected by the connecting portion can be two carbon-based particles, can be two metal-based particles, or can be carbon-based particles and metal-based particles. Compared with carbon-based particles, metal-based particles have larger expansion and contraction accompanying the charge and discharge of secondary batteries. It is believed that the connecting portion between metal-based particles and other active material particles (between carbon-based particles and metal-based particles, or between two metal-based particles) is more likely to be disconnected with the charge and discharge of secondary batteries than the connecting portion between two carbon-based particles. In this negative electrode, since the connecting portion has a first layer with excellent hardness and a second layer with excellent softness, it is possible to give the connecting portion appropriate strength and softness. Therefore, even if at least one of the two active material particles connected by the connecting portion is a metal-based particle, it is possible to suppress the disconnection of the connecting portion accompanying the charge and discharge of the secondary battery.

[0051] The content of PAA and SBR contained in the connecting portion, that is, PAA:SBR (volume ratio) is preferably 1:1.2 to 1:15, 1:1.25 to 1:12, or 1:1.3 to 1:10. As described in the examples below, the content of PAA and SBR contained in the connecting portion can be determined by dyeing PAA and SBR and observing the spectral distribution using SEM-EDX spectroscopy.

[0052] At least one of PAA and SBR that do not form a connecting portion may be arranged on the surface of the active material particles included in the active material layer. The PAA and SBR on the surface of the active material particles that do not form a connecting portion do not have a first layer and a second layer like the connecting portion, and PAA and SBR are preferably arranged so as to cover the surface of the active material particles independently.

[0053] The active material layer may contain a conductive aid. As the conductive aid, one or more carbon materials selected from fibrous carbon, carbon black (acetylene black, Ketjen black, etc.), coke and activated carbon can be cited. As the fibrous carbon, carbon nanotubes (hereinafter also referred to as "CNTs") can be cited. CNTs can be single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes such as double-walled carbon nanotubes (DWCNTs). As described above, the connecting portion has a structure that is not easy to disconnect and easy to follow the expansion and contraction of the active material particles accompanying the charging and discharging of the secondary battery, and can also connect two active material particles arranged at a distant position in the active material layer. The conductive aid can be arranged around the connecting portion to form a conductive path between the active material particles. Therefore, using a connecting portion having a first layer and a second layer, and a conductive aid present around the connecting portion, it is easy to form a good conductive path that is not easy to disconnect in the active material layer. Thus, a secondary battery with excellent cycle characteristics can be obtained.

[0054] The active material layer may contain carboxymethyl cellulose (CMC). CMC may be in the form of an acid or a salt, preferably in the form of a salt. By containing CMC, it is easy to form a connection portion uniformly in the active material layer.

[0055] The yield ring height measured by the stiffness test for the negative electrode is preferably less than 18 mm, less than 15 μm, less than 12 μm, 1 to 18 μm, 2 to 15 μm, or 2 to 12 μm. As described in the embodiments described later, a single-sided plate having an active material layer formed only on one side of the negative electrode collector is butted at both ends to form a ring rolled into a perfect circle in such a way that the outer peripheral surface becomes the active material layer. The yield ring height represents the height of the ring at the inflection point where the stress of the stiffness curve measured by pressing the outer peripheral surface of the ring rises and then drops sharply. The yield ring height can be adjusted, for example, according to the type of SBR contained in the active material layer.

[0056] (Method for manufacturing negative electrode)

[0057] Figure 1 : is a flowchart showing a method for manufacturing a negative electrode according to an embodiment. The method for manufacturing a negative electrode according to the embodiment can manufacture a negative electrode for a secondary battery, and can also manufacture the present negative electrode. The method for manufacturing a negative electrode includes: a first step of obtaining a first kneaded body (kneaded body), a second step of obtaining a slurry using the first kneaded body, and a third step of forming an active material layer using the slurry ( Figure 1). The first step includes the step of kneading active material particles, polyacrylic acid hydrate obtained by hydrating PAA (hereinafter also referred to as "PAA hydrate"), and water. The active material particles include carbon-based particles and metal-based particles. As active material particles (carbon-based particles and metal-based particles) and PAA, the above-mentioned materials can be cited. The second step of the method for manufacturing a negative electrode includes the step of adding SBR and water to the first kneaded body and kneading them.

[0058] When water is added to a mixture (mixed powder) obtained by mixing active material particles and PAA at a ratio contained in the first kneaded body and kneading is performed, and the solid content ratio when the torque reaches a maximum is set to the ideal solid content ratio B0 [weight %], the solid content ratio of the first kneaded body is (B0-5) to B0 [weight %], and the solid content ratio of the slurry is (B0-25) to (B0-10) [weight %].

[0059] The ideal solid content ratio B0 [wt %] is calculated as follows: when water is added to a mixture (mixed powder) of active material particles and PAA at the above ratio and kneaded, the water content at which the torque required for kneading reaches the maximum is defined as A0 [wt %], and the amount of water per 100 g of the above mixture (mixed powder) corresponding to the water content A0 [wt %] is defined as A1 [mL], and it can be calculated by the following formula. The ideal solid content ratio B0 [wt %] is, for example, 55 to 75%.

[0060] B0[weight%]=100-A0={100 / (100+A1)}×100

[0061] The solid content ratio of the first kneaded body is (B0-5) to B0 [weight %], can be (B0-4) to B0 [weight %], can be (B0-3) to B0 [weight %], or can be (B0-2) [weight %] or more and less than B0 [weight %]. The solid content ratio of the first kneaded body can be calculated as the weight ratio [weight %] of the solid component (components other than water) relative to the total weight of the first kneaded body. By kneading in a manner to obtain the first kneaded body within the above-mentioned solid content ratio range, the first layer of the connecting portion can be well formed between the active material particles.

[0062] The content ratio of PAA and water contained in the PAA hydrate is PAA: water (weight ratio), which can be 1:1 to 1:100, 1:1 to 1:50, 1:2 to 1:20, 1:5 to 1:10, or 1:1. The method for manufacturing a negative electrode may include, before the first step, a step of mixing PAA with water to hydrate PAA to obtain PAA hydrate. The mixing ratio of PAA and water used when hydrating PAA may be within the above-mentioned range of the content ratio of PAA and water contained in the PAA hydrate. By using PAA hydrate in the first step, the thickness (roughness) of the first layer formed in the connection portion between the active material particles can be increased.

[0063] The mixing process of the first step can be further performed by adding CMC. That is, in the first step, CMC can be added together with the active material particles, PAA hydrate and water for mixing. As CMC, the above-mentioned materials can be cited. Since the first step is a dry mixing step, the active material particles and PAA hydrate are easily agglomerated. By adding CMC in the first step, the aggregation of the active material particles and PAA hydrate can be suppressed, and the active material particles and PAA can be well dispersed. As a result, the first layer of the connecting portion can be uniformly formed between the active material particles in the active material layer.

[0064] When CMC is added and kneaded in the first step, the method for producing the negative electrode may include a step of dry-mixing the active material particles and CMC to obtain a mixed powder before the first step. In this case, the first step may be to knead the mixed powder, PAA hydrate and water to obtain a first kneaded body.

[0065] The kneading process of the first step can be further performed by adding a conductive auxiliary agent. That is, in the first step, a conductive auxiliary agent can be added together with the active material particles, PAA hydrate and water for kneading. As the conductive auxiliary agent, the above-mentioned materials can be cited. In the case where CMC and the conductive auxiliary agent are added and kneaded in the first step, the mixed powder, PAA hydrate, the conductive auxiliary agent and water can be kneaded in the first step. By kneading the conductive auxiliary agent in the first step, the conductive auxiliary agent can be arranged around the connecting portion, and a good conductive path can be formed in the active material layer.

[0066] The first step can be performed using a stirrer with a stirring blade. The rotation speed of the stirring blade in the first step is not particularly limited, and can be, for example, 40 to 70 rpm, 45 to 65 rpm, or 50 to 55 rpm. The kneading time in the first step can be, for example, 100 to 200 min, 20 to 120 min, or 30 to 100 min.

[0067] The second step is performed to adjust the solid content concentration of the slurry. The solid content ratio of the slurry is (B0-25) to (B0-10) [weight %], can be (B0-22) to (B0-11) [weight %], can be (B0-18) to (B0-12) [weight %], and can also be (B0-16) to (B0-11) [weight %]. The solid content ratio of the slurry can be calculated as the weight ratio [weight %] of the solid content (components other than water) relative to the total weight of the slurry.

[0068] The SBR added in the second step may be added in the form of an SBR aqueous solution. The second step may include: a step (2.1) of kneading the first kneaded body and water to obtain a second kneaded body, and a step (2.2) of mixing the second kneaded body and SBR (SBR aqueous solution). In the second step, since SBR and water are added to the first kneaded body, a second layer containing SBR can be formed on the surface of the first layer formed between the active material particles.

[0069] The second step can be carried out using a stirrer with a stirring blade. The rotation speed of the stirring blade in the second step is not particularly limited, and can be, for example, 10 to 40 rpm, 20 to 35 rpm, or 25 to 30 rpm. The stirring time in the second step can be, for example, 10 to 90 min, 15 to 60 min, or 20 to 50 min. The kneading time of step (2.1) can be, for example, 15 to 45 min, or 20 to 40 min. The mixing time of step (2.2) can be, for example, 1 to 20 min, or 5 to 15 min. The kneading time of step (2.1) can be longer than the mixing time of step (2.2).

[0070] The third step is a step of forming an active material layer using the slurry prepared in the second step. The third step may include applying the slurry on the negative electrode collector to form a coating layer, and drying the coating layer, and may further include a step of compressing the dried coating layer. As the negative electrode collector, the above-mentioned materials can be cited.

[0071] (Non-aqueous electrolyte secondary battery)

[0072] The non-aqueous electrolyte secondary battery of the present embodiment (hereinafter also referred to as "the present battery") comprises the present negative electrode, and generally comprises an electrode body containing the present negative electrode and a non-aqueous electrolyte. The present battery may have a battery case for accommodating the electrode body and the non-aqueous electrolyte. The battery case may include: an outer casing having an opening, and a sealing plate for sealing the opening. The outer casing and the sealing plate are preferably made of metal, and may be formed using aluminum, an aluminum alloy, iron or an iron alloy, and may be formed using an aluminum laminate film, for example. A resin sheet serving as an electrode holder may be arranged between the electrode body and the outer casing.

[0073] The electrode body may include the present negative electrode, the positive electrode and the separator. In the electrode body, the active material layer of the present negative electrode and the positive electrode active material layer of the positive electrode are opposed to each other via the separator. The electrode body may be a laminated type in which the present negative electrode, the positive electrode and the separator are laminated, or a wound type in which a laminated body in which the present negative electrode, the positive electrode and the separator are laminated is wound.

[0074] The positive electrode generally has a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is, for example, a metal foil made of aluminum materials such as aluminum and aluminum alloys. The positive electrode active material layer contains positive electrode active material particles, and may further contain a conductive material and a binder. Examples of positive electrode active material particles include layered or spinel lithium transition metal oxides (e.g., LiNiCoMnO2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiCrMnO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) particles. The lithium transition metal oxide may be a lithium nickel cobalt manganese composite oxide (NCM). As the conductive material, for example, carbon materials such as fibrous carbon (CNT (SWCNT, DWCNT)), carbon black (such as acetylene black, Ketjen black), coke, activated carbon, etc. may be cited. As the binder, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE) and SBR may be cited.

[0075] The spacer has a substrate, and may have a functional layer on at least one side of the substrate. The substrate may be a film made of a resin such as polyethylene, polypropylene, polyester, cellulose, polyamide, and a porous sheet such as a non-woven fabric. The substrate may have a single-layer structure or a multi-layer structure. As the functional layer, for example, an adhesive layer and a heat-resistant layer may be cited, and one or both of these may be included. The adhesive layer may be formed, for example, by an adhesive. The heat-resistant layer may include, for example, a filler and a binder.

[0076] The non-aqueous electrolyte preferably contains a supporting salt in a non-aqueous solvent such as an organic solvent. As supporting salts, LiPF6, LiBF4, LiClO4, LiFSO3, LiBOB (lithium bis(oxalate)borate) and the like can be cited. The non-aqueous electrolyte can include one or more supporting salts of these. As non-aqueous solvents, for example, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), butylene carbonate (BC) and diethyl carbonate (DEC) and the like can be cited. The non-aqueous electrolyte can include one or more non-aqueous solvents of these.

[0077] (Method for producing non-aqueous electrolyte secondary battery)

[0078] The manufacturing method of the battery includes the step of manufacturing the negative electrode by the manufacturing method of the negative electrode. The manufacturing method of the battery may further include the step of obtaining an electrode body using the negative electrode, the positive electrode and the separator, and the step of accommodating the electrode body and the non-aqueous electrolyte in a battery case.

[0079] Example

[0080] The present disclosure will be described in more detail below with reference to Examples and Comparative Examples. Figure 2 to Figure 5 These are SEM images of the active material layers of the negative electrodes prepared in Examples 1 and 2 and Comparative Examples 1 and 2.

[0081] [Example 1]

[0082] (Production of negative electrode)

[0083] Graphite particles were used as carbon particles, and Si and C composite particles (SiC composite particles) were used as metal particles. SWCNT was used as a conductive additive. Slurry (1) was prepared by the following procedure using a mixer (HIVIS MIX2P-1 manufactured by PRIMIX).

[0084] First, PAA powder and water are mixed at a ratio of PAA powder: water = 1: 1 (weight ratio) to obtain PAA hydrate. Carbon-based particles, metal-based particles and CMC are dry-mixed to obtain a mixed powder (1). PAA hydrate, mixed powder (1), SWCNT and water are kneaded at a solid content ratio of 65% by weight and a stirrer speed of 50 rpm for 90 minutes to obtain a first kneaded body (first step). Next, the first kneaded body and water are kneaded at a stirrer speed of 30 rpm for 30 minutes to obtain a second kneaded body, and an SBR aqueous solution is added to the second kneaded body, and mixed at a solid content ratio of 50% by weight and a stirrer speed of 30 rpm for 10 minutes to obtain a slurry (1) with a solid content ratio of 50% by weight (second step). The mixing ratio of the slurry (1) is graphite particles: SiC composite particles: SWCNT: CMC: PAA: SBR = 90: 10: 0.05: 1: 1: 1 (weight ratio).

[0085] When water is added to a mixture obtained by mixing graphite particles, SiC composite particles and PAA in a ratio contained in the first kneaded body and kneading is performed, the water content at which the torque required for kneading reaches the maximum is set as A0 [weight %], and the water amount per 100 g of the above-mentioned mixture (mixed powder) corresponding to the water content A0 [weight %] is set as A1 [mL]. The ideal solid content ratio (B0) calculated by the following formula is 65 weight %.

[0086] B0[weight%]=100-A0={100 / (100+A1)}×100

[0087] Therefore, in this embodiment, the solid content ratio of the first step is (B0) [weight %], and the solid content ratio of the slurry (1) is (B0-15) [weight %].

[0088] The slurry (1) obtained above was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector, dried, and compressed to obtain a negative electrode (1). The unit area weight of the active material layer of the negative electrode (1) (the total unit area weight of both sides) was 215 g / m 2 The thickness of the active material layer (per single side) is 135 μm, and the packing density of the active material layer is 1.60 g / cc. Figure 2 As shown, in the active material layer of the negative electrode (1), a thick columnar connection portion having a first layer and a second layer formed on the surface of the first layer is formed between two active material particles, and both ends of the first layer and the second layer contact the surface of the active material particles. Figure 2 Although the connection portions formed between the graphite particles and the SiC composite particles are shown, similar connection portions are also formed between the graphite particles and between the SiC composite particles.

[0089] (Production of positive electrode)

[0090] Lithium nickel cobalt manganese composite oxide (NCM) as positive electrode active material particles, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are used in a ratio of positive electrode active material particles: AB: PVdF = 100: 1: 1 (weight ratio), and they are mixed with N-methylpyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry is applied on an aluminum foil with a thickness of 15 μm as a positive electrode collector, dried, and compressed to obtain a positive electrode.

[0091] (Fabrication of non-aqueous electrolyte secondary battery)

[0092] The negative electrode and the positive electrode obtained in the above are respectively equipped with leads, and the negative electrode and the positive electrode are stacked with a separator to obtain an electrode body. The electrode body is inserted into an outer body composed of an aluminum laminate sheet and a non-aqueous electrolyte is injected, and the opening of the outer body is sealed to obtain a test battery (laminated battery) (1). The non-aqueous electrolyte uses a solution obtained by dissolving LiPF6 as a lithium salt in a mixed solvent at a concentration of 1 mol / L, and the mixed solvent contains ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of EC:EMC:DMC=30:30:40.

[0093] [Example 2]

[0094] The slurry (2) was prepared in the same manner as in Example 1 except that the type of SBR contained in the SBR aqueous solution was changed to obtain a negative electrode (2) and a test cell (2). The SBR used in this example is harder and less prone to cracking than the SBR used in Example 1. Figure 3 As shown, in the active material layer of the negative electrode (2), a thick columnar connection portion having a first layer and a second layer formed on the surface of the first layer is formed between two active material particles, and both ends of the first layer and the second layer contact the surface of the active material particles. Figure 3 Although connecting portions formed between graphite particles are shown, similar connecting portions are formed between SiC composite particles and between graphite particles and SiC composite particles.

[0095] [Comparative Example 1]

[0096] (Production of negative electrode)

[0097] The slurry (c1) was prepared by the following procedure to obtain the negative electrode (c1). In this comparative example, the same carbon-based particles, metal-based particles, PAA powder, SWCNT, SBR and agitator as those used in the preparation of the negative electrode in Example 1 were used.

[0098] First, carbon-based particles, metal-based particles, PAA powder and CMC are dry-mixed to obtain a mixed powder (c1). The mixed powder (c1), SWCNT, SBR aqueous solution and water are kneaded at a solid content ratio of 65 wt% to obtain a mixed body. Next, the mixed body is kneaded with water to obtain a slurry (c1) with a solid content ratio of 50 wt%. The mixing ratio of each component is the same as that in Example 1. Except for using slurry (c1) instead of slurry (1), the negative electrode (c1) is obtained according to the negative electrode preparation steps of Example 1. Figure 4 As shown, in the active material layer of the negative electrode (c1), a thin columnar connection portion having a single-layer structure formed of a mixture of PAA and SBR is formed between two active material particles. Figure 4 The connecting parts formed between the graphite particles are shown, and the connecting parts formed between the SiC composite particles and between the graphite particles and the SiC composite particles are also in the form of thin columns with a single-layer structure.

[0099] (Fabrication of non-aqueous electrolyte secondary battery)

[0100] A test cell (c1) was obtained according to the procedure for producing a nonaqueous electrolyte secondary battery of Example 1 except that the negative electrode (c1) was used instead of the negative electrode (1).

[0101] [Comparative Example 2]

[0102] (Production of negative electrode)

[0103] The slurry (c2) was prepared by the following procedure to obtain a negative electrode (c2). In this comparative example, the same carbon-based particles, metal-based particles, PAA powder, SWCNT, SBR and agitator as those used in the preparation of the negative electrode in Example 1 were used.

[0104] First, carbon particles, metal particles, PAA powder and CMC are dry-mixed to obtain a mixed powder (c2). The mixed powder (c2), SWCNT, SBR aqueous solution and water are kneaded at a solid content ratio of 50 wt% to obtain a slurry (c2) with a solid content ratio of 50 wt%. The mixing ratio of each component is the same as that in Example 1. Except for using slurry (c2) instead of slurry (1), the negative electrode production steps of Example 1 are followed to obtain the negative electrode (c2). Figure 5 As shown, the structure formed between two active material particles in the active material layer of the negative electrode (c2) is a partially disconnected column structure or a very thin column structure, and is a single-layer structure. Figure 5 Although the structure formed between graphite particles is shown, the structure formed between SiC composite particles and between graphite particles and SiC composite particles also has the same structure.

[0105] (Fabrication of non-aqueous electrolyte secondary battery)

[0106] A test cell (c2) was obtained according to the procedure for producing a non-aqueous electrolyte secondary battery of Example 1 except that the negative electrode (c2) was used instead of the negative electrode (1).

[0107] [Measurement of the connection part]

[0108] (Content of PAA and SBR)

[0109] The contents of PAA and SBR contained in the connecting portion were determined according to the following steps. PAA was dyed with osmium (Os) and SBR was dyed with ruthenium (Ru) by a dyeing method, thereby visualizing the binder component. Thereafter, the spectral distribution was observed using SEM-EDX spectroscopy to determine the contents (volume ratio) of PAA and SBR contained in the connecting portion. The results are shown in Table 1.

[0110] (Length and diameter)

[0111] The length and diameter of the connecting portion in the SEM image were measured, and the average values ​​thereof were taken as the length and diameter of the connecting portion.

[0112] [Evaluation of cycle characteristics]

[0113] Under the environment of 25°C, the test battery was charged to 4.15V and 0.1C by constant current and constant voltage charging (CCCV) with a current value of 0.2C, and then discharged (CC discharge) to 3V with a current value of 0.33C as one cycle, and the charge and discharge were repeated. According to the following formula, the discharge capacity of the 200th cycle relative to the discharge capacity of the first cycle was calculated as the cycle maintenance rate [%]. The results are shown in Table 1.

[0114] Cycle retention rate [%] = (discharge capacity at the 200th cycle / discharge capacity at the 1st cycle) × 100

[0115] [Stiffness test]

[0116] Peel off the active material layer on one side of the negative electrode, and cut a piece of 10mm wide x 80mm long from the single-sided plate in which the active material layer is formed only on one side of the negative electrode collector. In such a way that the outer peripheral surface of the cut single-sided plate becomes the active material layer, the two ends in the length direction are butted together and rolled into a perfect circle to make a measurement sample with an outer circumference of 80mm. Fix the butted part of the measurement sample to the lower plate of the ring stiffness tester, and clamp the measurement sample between the upper plate and the lower plate. Find the inflection point where the stiffness curve (stress generated in the measurement sample) measured by squeezing the outer peripheral surface of the measurement sample rises and then drops sharply, and measure the distance between the upper plate and the lower plate at the inflection point as the height of the yield ring. The results are shown in Table 1.

[0117] [Table 1

[0118]

[0119] Although the embodiments of the present invention have been described, the embodiments disclosed herein are illustrative in all aspects and should not be construed as limiting. The scope of the present invention is indicated by the scope of the claims, and is intended to include all changes within the meaning and scope equivalent to the scope of the claims.

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising an active material layer containing active material particles, The active material particles include carbon-based active material particles and metal-based active material particles. The active material layer has a connecting portion connecting two active material particles. The connecting portion includes a first layer and a second layer, the first layer includes at least one of polyacrylic acid and a salt thereof, and the second layer is formed on a surface of the first layer and includes styrene-butadiene rubber. The first layer and the second layer are both in contact with surfaces of the two active material particles connected by the connecting portion.

2. The negative electrode according to claim 1, wherein The carbon-based active material particles include graphite particles.

3. The negative electrode according to claim 1, wherein The metal active material particles include Si, SiO x and one or more particles of a complex of Si and C.

4. The negative electrode according to claim 1, wherein The connecting portion connects at least the carbon-based active material particles and the metal-based active material particles.

5. The negative electrode according to claim 1, wherein The active material layer further includes a conductive auxiliary agent.

6. The negative electrode according to claim 1, wherein The active material layer further includes carboxymethyl cellulose. 7 . A non-aqueous electrolyte secondary battery comprising the negative electrode according to claim 1 .

8. A method for producing a negative electrode, which is a method for producing a negative electrode for a non-aqueous electrolyte secondary battery, wherein the negative electrode has an active material layer containing active material particles, The method for manufacturing the negative electrode comprises: a first step of obtaining a kneaded body, a second step of obtaining a slurry using the kneaded body, and a third step of forming the active material layer using the slurry, The first step includes a step of kneading active material particles, polyacrylic acid hydrate and water, wherein the polyacrylic acid hydrate is obtained by hydrating at least one of polyacrylic acid and a salt thereof. The active material particles include carbon-based active material particles and metal-based active material particles. The second step includes adding styrene-butadiene rubber and water to the kneaded body and kneading the mixture. When water is added to a mixture obtained by mixing at least one of the polyacrylic acid and its salt and the active material particles at a ratio contained in the kneaded body and kneading the mixture, the solid content ratio at which the torque reaches a maximum is defined as an ideal solid content ratio B0 [wt %], The solid content ratio of the kneaded body is (B0-5) to B0 [weight %], The solid content ratio of the slurry is (B0-25) to (B0-10) [wt %].

9. The method for manufacturing a negative electrode according to claim 8, wherein: The kneading step in the first step is performed by further adding carboxymethyl cellulose.

10. The method for manufacturing a negative electrode according to claim 8, wherein: The kneading step in the first step is further performed by adding a conductive auxiliary agent.

11. The method for manufacturing a negative electrode according to claim 8, wherein: The carbon-based active material particles include graphite particles.

12. The method for manufacturing a negative electrode according to claim 8, wherein: The metal active material particles include Si, SiO x and one or more particles of a complex of Si and C. 13 . A method for producing a nonaqueous electrolyte secondary battery, comprising the step of producing a negative electrode by the method for producing a negative electrode according to claim 8 .

Citation Information

Patent Citations

  • Nonaqueous electrolytic secondary battery

    JP2015053152A

  • Negative electrode for secondary battery and production method therefor, secondary battery and production method therefor, battery pack, electric vehicle, power storage system, electric tool and electronic device

    WO2017026268A1